The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1021/acs.nanolett.5b00885
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Band Gap Emission by Hot Electron Injection in Metal/MoS2 and Metal/WSe2 Heterojunctions

Abstract: Transition metal dichalcogenides (TMDCs), such as MoS2 and WSe2, are free of dangling bonds and therefore make more "ideal" Schottky junctions than bulk semiconductors, which produce Fermi energy pinning and recombination centers at the interface with bulk metals, inhibiting charge transfer. Here, we observe a more than 10× enhancement in the indirect band gap photoluminescence of transition metal dichalcogenides (TMDCs) deposited on various metals (e.g., Cu, Au, Ag), while the direct band gap emission remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 42 publications
3
48
0
Order By: Relevance
“…The indirect bandgap of MoS 2 indicates that its Σ‐point is at a lower Schottky barrier height compared to the K‐point. Moreover, in the MoS 2 metal junctions sulfur atoms (S 3pz orbitals) can directly interact with the metal surface which favors the electron conduction into the Σ‐point and therefore the possibility arises of decaying K‐valley electrons to the Σ‐point . As the deposited Pt nanostrip can interact with the top Mo‐S layer there is a possibility of destabilization of the MoS 2 lattice.…”
Section: Resultsmentioning
confidence: 99%
“…The indirect bandgap of MoS 2 indicates that its Σ‐point is at a lower Schottky barrier height compared to the K‐point. Moreover, in the MoS 2 metal junctions sulfur atoms (S 3pz orbitals) can directly interact with the metal surface which favors the electron conduction into the Σ‐point and therefore the possibility arises of decaying K‐valley electrons to the Σ‐point . As the deposited Pt nanostrip can interact with the top Mo‐S layer there is a possibility of destabilization of the MoS 2 lattice.…”
Section: Resultsmentioning
confidence: 99%
“…It has further been shown that the emission is tunable between neutral excitons and trions [38,113]. Although monolayers are usually preferred for electroluminescent devices because of their direct band gap, EL has also been observed in TMD multilayers by carrier redistribution from the indirect to the direct valleys in a high electric field [118], by indirect valley filling [119], or by the injection of hot carriers from a metal/TMD junction [120].…”
Section: Electrically Driven Excitonic Light Emission Electroluminesmentioning
confidence: 99%
“…Monolayer TMDs are usually used for EL-devices because of their direct band gap. Light emission from multi-layer TMDs was reported by carrier redistribution from the indirect to the direct valleys in a high electric field [64], by filling the indirect valleys in the conduction and valence bands in an electric-double-layer transistor [65], or by the injection of hot electrons from metal/TMD junction [66].…”
Section: Light-emittersmentioning
confidence: 99%